ANALISIS PENGARUH FREE CASH FLOW DAN FINANCIAL LEVERAGE TERHADAP MANAJEMEN LABA DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Herlambang, Akbar Roy; H Halim, Edyanus; ', Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of Free Cash Flow to earnings management, the effect of Financial Leverage to earnings management, Good Corporate Governance as a moderating variable influence of Free Cash Flow and Financial Leverage effect on earnings management. The population in this study is a company in Jakarta Islamic Index are listed on the Indonesia Stock Exchange (BEI) in the period 2010-2015. The dependent variable in this study is the earnings management, while the independent variable is the Free Cash Flow and Financial Leverage. This study has a population of as many as 51 companies in Jakarta Islamic Index are listed on the Indonesia Stock Exchange 2011-2015 period. This study using purposive sampling techniques and sample that meets as many as 19 companies. The analysis used is regression panel data, Based on the results of these tests show that Free Cash Flow negatively and no significant effect on Earnings Management, Financial Leverage has effect and significant effect on Earnings Management, Good Corporate Governance does not moderate influenced the Free Cash Flow to the Earnings Management but not significantly, and Good Corporate Governance weakenly the effect of Financial Leverage to the Earnings Management and significantly.Keyword: Free Cash Flow, Financial Leverage, Earning Management, and Good Corporate Governance